Effect of Crystal Orientation and Conduction Band Grading of Absorber on Efficiency of Cu(In, Ga)Se2 Solar Cells Grown on Flexible Polyimide Foil at Low Temperature. Issue 26 (19th July 2018) - Kim, SeongYeon; Yoo, Hyesun; Rana, Tanka Raj; Enkhbat, Temujin; Han, Gyuho; Kim, JunHo; Song, Soomin; Kim, Kihwan; Gwak, Jihye; Eo, Young‐Ju; Yun, Jae Ho
Abstract: Flexible Cu(In, Ga)Se2 (CIGS) solar cells are developed on polyimide (PI) foil by using a three‐stage co‐evaporation method. To deposit CIGS on a PI substrate, low temperature deposition process (below 440 °C) is investigated. By optimizing the three‐stage process, power conversion efficiency (PCE) values of 12.1% and 13.6% are obtained at maximum process temperatures of 400 °C and 440 °C, respectively (without anti‐reflection coating). The CIGS absorber deposited at 400 °C is grown with (220)/(204) rather than (112) as its dominant growth orientation, accompanied by highly homogeneous crystal structure and phases. Admittance spectroscopy reveals that the defect levels were lower in the CIGS absorber with (220)/(204) dominant growth orientation, which could have contributed to the PCE of 12.1%. The CIGS solar cell deposited at a temperature of 440 °C exhibits worse defect characteristics compared to that fabricated at 400 °C. However, the CIGS solar cell fabricated below 440 °C exhibited marginal double‐grading of Ga/(Ga + In) in the absorber layer, which resulted in an improved PCE of 13.6%. This result implies that at a temperature below 440 °C, the double‐grading of Ga/(Ga + In) is the more dominant factor causing the PCE improvement above 13%. Abstract : A flexible CIGS solar cell grown on polyimide foil at low temperature shows a PCE of 13.6% (without anti‐reflection coating). A systematic characterization study reveals that crystal orientation accompanied by reduced defect states and the double‐graded energy band of the CIGS absorber improves the PCE of the flexible CIGS solar cell.